Simultaneous (166)Ho/(99m)Tc dual-isotope SPECT with Monte Carlo-based downscatter correction for automatic liver dosimetry in radioembolization - van Rooij, R. (EJNMMI Phys, 2020)
BACKGROUND: Intrahepatic dosimetry is paramount to optimize radioembolization treatment accuracy using radioactive holmium-166 microspheres ((166)Ho). This requires a practical protocol that combines quantitative imaging of microsphere distribution with automated and robust delineation of the volumes of interest. To this end, we propose a dual isotope single photon emission computed tomography (SPECT) protocol based on (166)Ho therapeutic microspheres and technetium-99 m ((99m)Tc) stannous phytate, which accumulates in healthy liver tissue. This protocol may allow accurate and automatic estimation of tumor-absorbed dose and healthy liver-absorbed dose. The current study focuses on a Monte Carlo-based reconstruction framework that inherently corrects for scatter crosstalk between the (166)Ho and (99m)Tc imaging. To demonstrate the feasibility of the method, it is evaluated with realistic phantom experiments and patient data. METHODS: The Utrecht Monte Carlo System (UMCS) was extended to include detailed modeling of crosstalk interactions between (99m)Tc and (166)Ho. First, (99m)Tc images were reconstructed including energy window-based corrections for (166)Ho downscatter. Next, (99m)Tc downscatter in the 81-keV (166)Ho window was Monte Carlo simulated to allow quantitative reconstruction of the (166)Ho images. The accuracy of the (99m)Tc-downscatter modeling was evaluated by comparing measurements with simulations. In addition, the ratio between (99m)Tc and (166)Ho yielding the best (166)Ho dose estimates was established and the quantitative accuracy was reported. RESULTS: Given the same level of activity, (99m)Tc contributes twice as many counts to the 81-keV window than (166)Ho, and four times as many counts to the 140-keV window, applying a (166)Ho/(99m)Tc ratio of 5:1 yielded a high accuracy in both (166)Ho and (99m)Tc reconstruction. Phantom experiments revealed that the accuracy of quantitative (166)Ho activity recovery was reduced by 10% due to the presence of (99m)Tc. Twenty iterations (8 subsets) of the SPECT/CT reconstructions were considered feasible for clinical practice. Applicability of the proposed protocol was shown in a proof-of-concept case. CONCLUSION: A novel (166)Ho/(99m)Tc dual-isotope protocol for automatic dosimetry compensates accurately for downscatter and allows for the addition of (99m)Tc without compromising (166)Ho SPECT image quality.